BS 6833-6:1992. Apparatus using cordless attachments (excluding cellular radio apparatus) for connection to analogueinterfaces of public switched telephone networks. Specification for cordless portable parts and cordless fixed parts asseparate stand alone items of apparatus. (31st October 1992) - British Standards Institution,
No abstract available